1985
DOI: 10.1055/s-2007-999946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Intravenous Infusions on Fetal Extracellular Fluid Composition in Pregnant Ewes

Abstract: Infusion of intravenous solutions to women in labor is common clinical practice. Since these infusions may change the volume and electrolyte balance between the mother and fetus, we investigated the influence of acute maternal volume expansion upon fetal and maternal fluid and electrolyte equilibrium in the chronically catheterized fetal lamb. Paired measurements of maternal and fetal plasma sodium and potassium concentrations, osmolality, and colloid osmotic pressure (COP), plus measurements in the fetal-plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…2000). This value is still well in excess of the maternal plasma COP before hemorrhage for the sheep in this study (approximately 20 mm Hg) and previously reported normal values (Golden et al. 1985; Layon & Gallagher 1987).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…2000). This value is still well in excess of the maternal plasma COP before hemorrhage for the sheep in this study (approximately 20 mm Hg) and previously reported normal values (Golden et al. 1985; Layon & Gallagher 1987).…”
Section: Discussionsupporting
confidence: 77%
“…In sheep, during late gestation (128–133 days), maternal COP is usually 6 mm Hg greater than fetal COP (Golden et al. 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation